Synthesis and application of (18F) fluorodeoxyglucose in oncology diagnosis - Mateusz Wędrowski; Paweł Waśniowski; Ewelina Wędrowska; Elżbieta Piskorska; Jolanta Czuczejko; Bogdan Małkowski; Walery Żukow (Kazimierz Wielki University, 2017)
[18F] Fluorodeoxyglucose ([18F] FDG) is the most commonly used radiopharmaceutical in clinical positron emission tomography (PET) in oncology. Cancer cells create their own specific microenvironment to survive and grow. Specific tumor microenvironment contributes to cancer metabolic reprogramming. Therefore, even with sufficient oxygen availability, cancer cells choose anaerobic glycolysis. Cancer cells compensate less energy efficient process by increasing the intensity of anaerobic glycolysis. Tumor cells have a high rate of metabolism and because of this, they take up more of the radioactive glucose (FDG). This makes the tumor cells appear more visible than other areas on the PET scan pictures. This paper presents nucleophilic synthesis of the [18F] FDG marker and basics of tumor development which can affect the [18F] FDG biochemical significance. Reference was made to clinical images obtained in PET technology using the [18F] FDG radiopharmaceutical.